ANALISIS PELAKSANAAN USAHA MIKRO KECIL MENENGAH (UMKM) DI PESANTREN BEQURANIC DITINJAU DARI HUKUM EKONOMI SYARIAH - Muhammad Khairul; Ahmad Shirotol; Susilawati; Ridwan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This Research is to determine the implementation of Micro and Small Enterprises (UMKM ) at the Bequranic Islamic Boarding School in terms of Sharia Economic Law. The data used by researchers uses qualitative data. Researchers use primary data which takes objects and subjects directly to the research site. The subjects in this research were UMKM at the Bequranic Islamic Boarding School. The object of this research is the UMKM community. The results of this research are that the development of Micro, Small and Medium Enterprises (UMKM) can be a driving factor for regional and national economic growth, as well as assisting in alleviating poverty and unemployment in certain areas. From the perspective of sharia economic law, its role is to regulate economic activities in accordance with sharia principles and values, such as production, distribution and consumption so that they comply with sharia economic principles. And also the implementation of transactions in UMKM applies sharia economics as the basis for carrying them out, such as buying and selling with mu'athah contracts and so on.